Evaluasi Sistem Informasi Layanan Antrian Paspor Online Menggunakan Framework Information Technology Infrastructure Library V3 - Zammy Lunni (Syntax Corporation Indonesia, 2023)
Palembang Class 1 Immigration Office is a service provider agency in the immigration sector that has the authority to arrange passports or Travel Letters of the Republic of Indonesia (SPRI). In meeting the needs of the community in passport processing, Palembang Class 1 Immigration Office has implemented an Online Passport Queuing Service System. Until now, the system still experiences problems such as errors in the system, exhausted quotas, inappropriate applicant NIK, slow access to the system, and system handling that always involves the Immigration Head Office. Therefore, an evaluation of the online passport queue service information system is needed which can be used as a benchmark for the sustainability of the system. The framework used is the Information Technology Infrastructure Library (ITIL) V3 framework with the domain of Service Operation and Continual Service Improvement. This research was conducted by distributing questionnaires, interviews and observations to obtain maturity level scores. The results of the maturity level calculation in the Service Operation (SO) domain show that the average value of maturity level in the SO domain is 3.49 or is at level 3 (Define Process) and for the Continual Service Improvement (CSI) domain is 3.47 or is at level 3 (Define Process). From the evaluation results of the Online Passport Queuing Service System based on the maturity level calculation, several recommendations for the Service Operation (SO) and Continual Service Improvement (CSI) domains can be taken into consideration in improving service operations and improving the Online Passport Queuing Service System on an ongoing basis.